ANALISIS PENDAPATAN USAHA TANI DAN MARGIN PEMASARAN CABAI RAWIT DI KELURAHAN TRIMULYO KAPANEWON SLEMAN KABUPATEN SLEMAN - Putri Hastuti, Benilda Alianca; Anggraeni, Rini; Kadarso, Kadarso; Subeni, Subeni (Fakultas Pertanian, Universitas Janabadra, 2024)
This research was conducted to know: (1) cayenne pepper farming income (2) the feasibility of cayenne pepper farming, (3) the marketing margin of cayenne pepper farming in Trimulyo Kapanewon Sleman Village, Sleman Regency. The basic method used in this research is quantitative, the research location is determined by purposive sampling. Respondent farmers were determined by random sampling method and respondent traders were selected by snowball sampling method. The results showed that: (1) the average income of cayenne pepper farming in Trimulyo Village is IDR 30,286,224 per farm per year or IDR 242,462,702 per hectare per year with an average total expenditure cost of IDR 5,563,776 per farm per year or IDR 43,194,669 per hectare per year. (2) Cayenne Pepper farming is feasible because it has an R/C value of 4.36. (3) The marketing margin value of the first level channel is IDR 2,792 per kilogram, while in the second level channel, a margin value of IDR 4,083 per kilogram is obtained, and the third level channel is Rp 9,083 per kilogram.